2002
DOI: 10.1046/j.1365-2893.2002.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon retreatment reduces or delays the incidence of hepatocellular carcinoma in patients with chronic hepatitis C

Abstract: Inhibition of hepatocarcinogenesis is a crucial issue in treating chronic hepatitis C patients, especially those who do not respond completely to interferon therapy. Interferon has been reported to reduce the incidence of hepatocellular carcinoma (HCC) not only in sustained virological responders but also in transient biochemical responders. However, the incidence of HCC increases in 5 years or more after interferon therapy in transient biochemical responders. The aim of this study is to assess whether interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
(45 reference statements)
2
17
0
1
Order By: Relevance
“…These patients have lower SVR rates to peginterferon plus ribavirin [45] and, as we have already shown above, higher risk of HCC. Perhaps this explains the results of a study by Hino et al [46], who showed that retreatment reduces or delays the incidence of HCC in a population predominantly with early stage of liver fibrosis.…”
Section: Discussionmentioning
confidence: 94%
“…These patients have lower SVR rates to peginterferon plus ribavirin [45] and, as we have already shown above, higher risk of HCC. Perhaps this explains the results of a study by Hino et al [46], who showed that retreatment reduces or delays the incidence of HCC in a population predominantly with early stage of liver fibrosis.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that gender, age, fibrosis stage, alanine aminotransferase, and interferon regimen are important pretreatment predictors of hepatocarcinogenesis [9,10,17]. In the present study 2 based on the patients with compensated cirrhosis, higher age and aspartate aminotransferase were associated with higher hepatocarcinogenesis rates in the whole population sample and in the sample which excluded patients who showed sustained virological response following additional treatment.…”
Section: Discussionmentioning
confidence: 44%
“…Recently, the therapeutic effectiveness of interferon treatment, which is the only treatment that can completely cure chronic hepatitis C, has been shown to increase when used in combination with ribavirin [5][6][7][8]. As interferon treatment has also been proven to reduce the risk of HCC [9][10][11], interferon treatment has been actively administered for chronic hepatitis C. However, interferon treatment has various adverse events that may prevent completion of the full treatment regimen. These include psychiatric adverse events, especially depression, which often leads to a discontinuation of interferon treatment [12][13][14][15][16][17][18] pegylated interferon-α-2b and ribavirin combination treatment has been reported to range from 29 to 36% [5][6][7].…”
Section: Introductionmentioning
confidence: 99%